Forecasting assessment of dental care availability for the population of Ukraine in the conditions of healthcare reform (discussion) - Mochalov Юрій Олександрович; Stupnytskyi Ростислав Миколайович; Shupiatskyi Ілля Михайлович; Molozhanov Ігор Олексійович; Keyan Давід Миколайович (Actual Dentistry, 2021)
In modern conditions dental treatment is one of the most common types of medical care in Ukraine, only 7.00 % of the young population are dentally healthy. During 2015–2019 the general practice of using 3.91 % of the consolidated state budget for health care for dental care was determined, mainly such funds were used for the maintenance of dental health care establishments. Resolution of the Cabinet of Ministers of Ukraine «Some issues of implementation of the program of state guarantees of medical care in 2020» from February 5, 2020 for № 65 provides the calculation of the tariff for dental services in the amount of UAH 9.19 per unit. Preliminary calculations indicate that comparing to 2019 during 2020 the state financial support of dental care will be reduced by 3444.20 million UAH (68.60 %). There are reasonable doubts about the rationality of the design of the Medical Guarantee Program in terms of treatment of dental diseases which carries the risk of further increase in dental morbidity and reduced availability of dental care for population.